2013
DOI: 10.1111/ijfs.12455
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of an omega‐3‐rich algal oil is improved by nanoemulsion technology using yogurt as a food vehicle

Abstract: Main title: The bioavailability of an omega-3 rich algal oil is improved by nanoemulsion 1 technology using yogurt as a food vehicle. lipid-based nutrients. This study examined whether ingestion of an omega-3 algal oil nanoemulsion 25 led to improved bioavailability compared to the bulk oil. Eleven subjects completed a single-blind, 26 randomised crossover trial, with a 21-day washout between interventions. Results demonstrated 27 LC3PUFA absorption from the nanoemulsion was significantly higher than the bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 41 publications
(71 reference statements)
1
28
0
Order By: Relevance
“…16 Microencapsulated emulsions for food applications have previously been discussed in detail elsewhere and will therefore not be reviewed further here. [73][74][75][76] None of these products requires the delivery system to be optically transparent, and therefore emulsions or nanoemulsions could be used, although there may be some advantages in terms of long-term stability and bioavailability from using nanoemulsions. Fortified nanoemulsions could be introduced into food systems such as beverages, salad dressings, sauces, dips, and desserts.…”
Section: Applications Of Nanoemulsions In Foods and Beveragesmentioning
confidence: 99%
“…16 Microencapsulated emulsions for food applications have previously been discussed in detail elsewhere and will therefore not be reviewed further here. [73][74][75][76] None of these products requires the delivery system to be optically transparent, and therefore emulsions or nanoemulsions could be used, although there may be some advantages in terms of long-term stability and bioavailability from using nanoemulsions. Fortified nanoemulsions could be introduced into food systems such as beverages, salad dressings, sauces, dips, and desserts.…”
Section: Applications Of Nanoemulsions In Foods and Beveragesmentioning
confidence: 99%
“…However, to our knowledge, information on the use of seaweeds for the supplementation of dairy products is lacking. Cottage cheese supplementation with kombu and wakame (Lalic & Berkovic, ) and yogurt supplementation with an omega‐3‐rich algal oil (Lane et al ., ) have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoemulsions, similar to conventional oil‐in‐water emulsion systems but with considerably smaller droplet sizes, can be used to incorporate lipid‐based components into aqueous foods . The use of nanoemulsions offers potential benefits, including increases in water dispersibility of oils, good physical and chemical stability, and improved bioavailability of various hydrophobic lipid components . However, utilisation of LCn3PUFA rich oils in nanoemulsions may further promote lipid oxidation in these already vulnerable oils.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a 50% (w/w) system is less likely to have a detrimental effect on food matrices than systems with lower oil loads because lower volumes of nanoemulsion can be added to achieve optimum enrichment levels . The systems were also demonstrated to significantly increase the bioavailability of total LCn3PUFA and DHA in a pilot randomised cross‐over trial, although additional larger, longer studies are needed to further ratify these findings. A preliminary evaluation to analyse total oxidation values (totox) indicated that these systems remained within safe ranges when stored at 4 °C for 37 days .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation